Investigating the Learning Gaps of Senior-secondary Children through Original (Real-life) Biological Images: What Really Lacks? - Roy , Anirban; Singh, Sushmita (Voices of Teachers and Teacher Educators, 2021)
The dismal learning levels of students in our school(s) posit a putative question on the institutional failure of the Nation’s education system. But this comes as no surprise, given the prevailing priorities of our education system lie only with rote memorization and good score(s) in the examinations. In pursuit of finishing the syllabus within a stipulated time, teachers often completely ignore the “learning gaps” being imbibed by the child. One of the more consequential features of learning gaps is their tendency, if left unaddressed, to compound over time and become more severe and pronounced, which can increase the chances that a student will struggle academically and socially or even drop out of school. Given diagrams as an imperative tool in the assessment process of learning gaps, senior secondary level Class XII students were given a picture-based questionnaire containing 16 original (real-life) images of biological entities and events; each of the images (microscopic and macroscopic) was followed by blank spaces for identification and labelling. The students were asked to identify the coloured images and write their responses. The student’s responses highlighted the gaps and errors regarding the concerned topics that have formed over the years. It was followed by an open-ended interview to perceive the latent stimulus that drove the responses of the students for the images. The students’ responses revealed some pioneering observations that subtly unveil the need for inclusion of the original (real-life) images in the science textbooks, in addition to the textbook images.